Morphological and molecular determination of a new Viola species (Violaceae) from Turkey - Düşen, Olcay; Göktürk, Ramazan Süleyman; Kaya, Ergun; Sarpkaya, Uygar; Gürcan, Betül (Phytotaxa, 2018)
Viola denizliensis is described as a new species from South-West Anatolia. The species grows on serpentinite stony slopes in Bozdağ Mountain in Denizli. It belongs to Viola sect. Melanium and is close to V. dirimliensis and V. kitaibeliana. Viola denizliensis can be readily distinguished from related species by morphological and molecular characters. Comments on descriptive and diagnostic characters, distribution and ecology, phenolgy and proposed conservation status for this new species are given in the present study. Morphological affinities and ISSR-based molecular relationships between V. denizliensis and related species are also discussed.